2013
DOI: 10.1515/jpem-2012-0408
|View full text |Cite
|
Sign up to set email alerts
|

Turner Syndrome and apparent absent uterus: a case report and review of the literature

Abstract: We report on a patient who initially presented with delayed puberty and an absent uterus on imaging with ultrasound and MRI. She was subsequently diagnosed with Turner Syndrome. Turner Syndrome typically presents with early loss of ovarian function and should be considered when primary ovarian insufficiency is present with apparent absent uterus on imaging. Follow-up imaging of the apparent absent uterus post-estrogen replacement therapy is important to confirm a normal uterus. A diagnosis of an absent uterus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…The genetic background is variable, the most frequent karyotypes are: 45,X (~50%), karyotypes with an isochromosome of X (i(Xq) or i(Xp)), the mosaic 45,X/46XX (%30), and karyotypes containing an entire or parts of Y chromosome [111,112]. …”
Section: Brachydactyly Type E As Part Of Syndromesmentioning
confidence: 99%
See 3 more Smart Citations
“…The genetic background is variable, the most frequent karyotypes are: 45,X (~50%), karyotypes with an isochromosome of X (i(Xq) or i(Xp)), the mosaic 45,X/46XX (%30), and karyotypes containing an entire or parts of Y chromosome [111,112]. …”
Section: Brachydactyly Type E As Part Of Syndromesmentioning
confidence: 99%
“…The main features are short stature (90-100%), gonadal dysgenesis, pubertal delay, primary amenorrhea (85%), estrogens insufficiency, cardiac anomalies and/or other congenital malformations like brachydactyly E (see Figure one at Bondy [113]) [111,112,114-116]. Other frequent features are: lymphedema, congenital malformations of the urinary system (30-40%), abnormalities of the external ocular appendages, (epicanthal folds, ptosis, hypertelorism, upward slanting palpebral fissures), strabismus and hypermetropia (25–35%), hearing problems and ear malformations, dysmorphic craniofacial features, abnormalities in tooth development and morphology (early eruption), melanocytic nevi, normal GH secretory pattern, altered liver enzymes¸ decreased bone mineral density, etc.…”
Section: Brachydactyly Type E As Part Of Syndromesmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because such treatment strategy may have adverse effects on the psychosocial health and bone metabolism of patients by delaying pubertal development (9,18,19). Akierman et al (20) reported a patient who presented with delayed puberty and an absent uterus on imaging who was subsequently diagnosed with TS. In this patient, the uterus became visible approximately 8 months after beginning estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%